A Two-Stage Process for Differentiation of Wharton's Jelly-Derived Mesenchymal Stem Cells into Neuronal-like Cells - Zaffar Equbal; Prakash N. Baligar; Madhulika Srivastava; Asok Mukhopadhyay (Hindawi Limited, 2021)
With no permanent cure for neurodegenerative diseases, the symptoms reappear shortly after the withdrawal of medicines. A better treatment outcome can be expected if the damaged neurons are partly replaced by functional neurons and/or they are repaired using trophic factors. In this regard, safe cell therapy has been considered as a potential alternative to conventional treatment. Here, we have described a two-stage culture process to differentiate Wharton Jelly mesenchymal stem cells (WJ-MSCs) into neuronal-like cells in the presence of various cues involved in neurogenesis. The fate of cells at the end of each stage was analyzed at the morphometric, transcriptional, and translational levels. In the first stage of priming, constitutively, wingless-activated WJ-MSCs crossed the lineage boundary in favor of neuroectodermal lineage, identified by the loss of mesenchymal genes with concomitant expression of neuron-specific markers, like SOX1, PAX6, NTRK1, and NEUROD2. Neuronal-like cells formed in the second stage expressed many mature neuronal proteins like Map2, neurofilament, and Tuj1 and possessed axon hillock-like structures. In conclusion, the differentiation of a large number of neuronal-like cells from nontumorigenic and trophic factors secreting WJ-MSCs promises the development of a therapeutic strategy to treat neurodegenerative diseases.